Concordance of TST and QFT-Plus, Sensitivity and Specificity of TST and QFT-Plus in Detection of LTBI in MDR TB Contact - Rullyano Hardian; Reviono Reviono; Harsini Kusumo; Yusup Subagio Sutanto (Jurnal Respirologi Indonesia, 2022)
Background: Tuberculosis (TB) is an infectious disease and the main cause of world health problems. Not all individuals infected with Mycobacterium tuberculosis (Mtb) develop active TB. Latent tuberculosis infection (LTBI) is a state of persistent immune response to stimulation of the Mtb antigen with no evidence of clinically manifest active TB. Closed contact and household contact with MDR TB patients increases the risk of MDR TB transmission. There is no gold-standard test for LTBI. Tuberculin Skin Test (TST) and Quantiferon Gold Plus (QFT-Plus) examinations are used for LTBI diagnosis.Methods: A cross-sectional diagnostic test of 32 MDR TB contacts, consisting of 16 household contacts and 16 close contacts, was conducted in April 2020 at Dr. Moewardi Surakarta Hospital.Results: Positive TST results among MDR TB contacts were 18.8%, while QFT-Plus positive was 25%. The concordance level of TST and QFT-Plus was nearly perfect (κ=0.818, p<0.001). The sensitivity and specificity of QFT-Plus with household contacts as the gold standard were 37.5% and 87.5%, respectively. The sensitivity and specificity of TST with household contacts as the gold standard were 25% and 87.5%, respectively.Conclusion: The concordance level of TST and QFT-Plus in the detection of LTBI in MDR TB contacts was very good. The TST can be used in place of QFT-Plus although QFT-Plus has better sensitivity. Both tests are useful for confirming TB infections. Both of these tests are not diagnostic, however they can be used to screen for LTBI in MDR TB contacts.